Kompetensi Guru Dalam Perencanaan Pembelajaran Pendidikan Agama Kristen: Teacher Competence in Lesson Planning of Christian Religious Education - Junita Purba; Youke L. Singal; Wahyu Bintoro; Beanto Benny (Perkumpulan Teolog Agama Kristen Indonesia, 2023)
The main purpose of education is to develop the morale of students. Therefore, teachers must imitate good attitudes, actions, and words to students so that they imitate them. Christian education is the process of transmitting Christian knowledge to practice Christian teachings. In schools, the role of the PAK teacher is urgently needed. A PAK teacher is someone who provides knowledge about Christianity that is based on the Bible, centered on Jesus Christ, and depends on the Holy Spirit to students in activities teaching learning, so that students can know God and His love which is done in the form of teaching. Public and private schools must develop teacher professional competence. PAK teachers are the ability of PAK teachers to bring students to understand and practice the religious values ​​they have learned by relying on high abilities and character and referring to the figure of Jesus as the Great Teacher. Teacher competence can contribute to improving learning achievement, being able to be an active role model, creative, innovative and have high integrity in school. Policies to improve the quality of education and teaching must always be pursued by various parties, both the government and other components involved in the process. The teacher as one of the components in it has great duties and responsibilities. Because the future of a nation is determined by qualified teachers. These duties and responsibilities do not only make students know and understand the teaching materials provided but can make students become educated human beings who understand their role as humans, so that they are beneficial for themselves and the surrounding environment. Contribution: This study contributes a comprehensive framework of PAK teacher competencies—pedagogical, professional, personal, social, and spiritual—integrated into lesson planning to shape students' Christ-like character and improve learning effectiveness in schools. Tujuan utama pendidikan adalah mengembangkan moral peserta didik. Oleh karena itu, guru harus mencontoh sikap, perbuatan dan ucapan yang baik kepada peserta didik sehingga mereka meneladaninya. Pendidikan Kristen adalah proses transmisi pengetahuan Kristen untuk mengamalkan ajaran Kristen. Di sekolah sangat perlu peran Guru PAK. Guru PAK adalah seorang yang memberikan ilmu pengetahuan tentang agama Kristen yang berdasarkan Alkitab, berpusat pada Yesus Kristus, dan bergantung pada Roh Kudus kepada peserta didik dalam kegiatan belajar mengajar, agar para peserta didik dapat mengenal Allah dan kasih-‐‑Nya yang dilakukan dalam bentuk pengajaran. Sekolah negeri maupun swasta harus mengembangkan kompetensi professional guru. Guru PAK adalah kemampuan guru PAK membawa peserta didik memahami serta menjalankan nilai-nilai agama yang dipelajarinya dengan mengandalkan kemampuan dan karakter yang tinggi dan mengacu pada sosok Yesus sebagai Guru Yang Agung. Kompetensi guru dapat memberikan kontribusi atas peningkatan prestasi belajar mampu menjadi teladan aktif kreatif inovatif dan mempunyai integritas yang tinggi di sekolah. Kebijakan peningkatan mutu pendidikan dan pengajaran harus selalu diupayakan oleh berbagai pihak, baik pemerintah maupun komponen lain yang terlibat dalam proses tersebut. Guru sebagai salah satu komponen di dalamnya memiliki tugas dan tanggung jawab yang besar. Karena masa depan suatu bangsa ditentukan oleh guru yang berkualitas. Tugas dan tanggung jawab tersebut tidak hanya sekedar membuat peserta didik menjadi tahu dan memahami bahan ajar yang diberikan, tetapi dapat menjadikan peserta didik menjadi manusia terdidik yang memahami perannya sebagai manusia, sehingga bermanfaat bagi diri dan lingkungan sekitarnya. Kontribusi: Penelitian ini memberikan kontribusi berupa kerangka kompetensi guru PAK (pedagogik, profesional, kepribadian, sosial, dan kerohanian) yang terintegrasi ke dalam perencanaan pembelajaran untuk membentuk karakter peserta didik serupa Kristus dan meningkatkan efektivitas pembelajaran di sekolah.